Parametrization of the dying brain: A case report from ICU bed-side EEG monitoring - Sebastian Zinn; Srdjan Z. Dragovic; Jan A. Kloka; Laurent M. Willems; Sebastian Harder; Stephan Kratzer; Kai D. Zacharowski; Gerhard Schneider; Paul S. García; Matthias Kreuzer (NeuroImage)
Background: Cortical high-frequency activation immediately before death has been reported, raising questions about an enhanced conscious state at this critical time. Here, we analyzed an electroencephalogram (EEG) from a comatose patient during the dying process with a standard bedside monitor and spectral parameterization techniques. Methods: We report neurophysiologic features of a dying patient without major cortical injury. Sixty minutes of frontal EEG activity was recorded using the Sedline™ monitor. Quantitative metrics of the frequency spectrum, the non-oscillatory 1/f characteristic, and signal complexity with Lemple-Ziv-Welch and permutation entropy were calculated. In addition to comparing the EEG trajectories over time, we provide a comparison to EEG records obtained from other studies with well-known vigilance states (sleep, anesthesia, and wake). Results: Although we observed changes in high-frequency activation during the dying process, larger alterations of the aperiodic EEG components were also noted. These changes differed dramatically when compared to EEG records representative of wake, slow-wave sleep, or anesthesia. Although still fundamentally unique, the neuronal activity present in the dying brain is more similar to REM sleep than any other state we tested. Conclusion: Even in patients with coma, temporal dynamics in quantitative EEG features (including the aperiodic components) can be observed in the final hour before death.